(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and Objectives: - The safety of Pregabalin and Nortriptyline have been proved individually in chronic low backache withradiculopathy. However, there are limited numberof studies comparing the tolerability of Pregabalin and Nortriptyline in chronic lowbackachewith radiculopathy. Hence the present study is designed to determine the tolerability of Pregabalin versus Nortriptyline. It isan prospective observational study.Methods: - Patients with chronic low backache with radiculopathy 15–60 years of age withoutspecific cause and significantneurological deficit were included. Patients were followed up at2 and 4 weeks and their side effect were noted.Results: - There was no statistical difference between pregabalin and nortriptyline groups in terms of visual analogue scale for painscore, from baseline to 2 weeks and from baseline toweek 4. The incidence of side effects were statistically less in the nortriptylinegroup compared to pregabalin group.From the results of the present study it can be concluded that both pregabalin and nortriptyline are effective in the treatment of chroniclow backache with radiculopathy withradicular pain but incidence of adverse events are more with the pregabalin compared tonortriptyline.Conclusion: - Anticonvulsants and TCAs are very effective in moderate to severe pain whilethe other drugs like NSAIDs and opiodsare more effective in mild to moderate pain.